2014
DOI: 10.4161/hv.27532
|View full text |Cite
|
Sign up to set email alerts
|

Current and potential immune therapies and vaccines in the management of psoriasis

Abstract: Psoriasis is a chronic, immune skin disease associated with significant morbidity. Development of psoriasis is influenced by numerous genes, one allele is HLA-CW*0602. Other genes and single nucleotide polymorphisms affect immunologic pathways and antimicrobial peptide synthesis. Dendritic cells initiate psoriasis by activating T-cells toward a Th1 and Th17 response, with increased cytokines including TNF-α, IL-6, -12, -17, -22, and -23. IL-22 appears to promote keratinocyte dedifferentiation and increased ant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 157 publications
0
9
0
Order By: Relevance
“…Mild psoriasis is often treated with topical corticosteroids and vitamin D analogs (Papp et al, 2011). However, around 18e25% of patients with psoriasis have moderate-to-severe disease (Helmick et al, 2014;National Psoriasis Foundation, 2019b), and these patients often require further treatment including phototherapy and systemic treatment with immunosuppressive medications (Kaffenberger et al, 2014;Mrowietz et al, 2011;Papp et al, 2011;Papp et al, 2016a).…”
Section: Introductionmentioning
confidence: 99%
“…Mild psoriasis is often treated with topical corticosteroids and vitamin D analogs (Papp et al, 2011). However, around 18e25% of patients with psoriasis have moderate-to-severe disease (Helmick et al, 2014;National Psoriasis Foundation, 2019b), and these patients often require further treatment including phototherapy and systemic treatment with immunosuppressive medications (Kaffenberger et al, 2014;Mrowietz et al, 2011;Papp et al, 2011;Papp et al, 2016a).…”
Section: Introductionmentioning
confidence: 99%
“…The progression in the enlightenment of the immunopathogenesis of psoriasis may provide new therapeutic options that do not have immunosuppressive side effects. Vaccination is a progressing therapy option for psoriasis and the other chronic inflammatory disorders such as multiple sclerosis, rheumatoid arthritis and atherosclerosis, which are termed as noncommunicable diseases [1,45,46]. It has clearly demonstrated that vaccines have the ability to activate effectors such as dendritic cells and T lymphocytes, which are also involved in psoriasis pathogenesis [41].…”
Section: Therapeutic Effects Of Vaccines On Psoriasismentioning
confidence: 99%
“…Vaccines are recommended for psoriasis patients due to their susceptibility to infections [12]. The data emphasize that especially some types of vaccines may trigger an exacerbation of psoriatic skin lesions or induce improvement in psoriasis [1,13].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations